Things too huge to fix by saying sorry - Vaught, Susan, 1965- (Simon & Schuster Books for Young Readers, 2017)
Dani is the biracial granddaughter of black scholar and writer Ruth Beans, a former civil rights activist who is now succumbing to Alzheimer's. Dani's friend Mac is the white grandson of Ruth's estranged friend and Pulitzer Prize-winning novelist, Avadelle Richardson. When Dani's grandmother gives her a mysterious envelope and a key, the middle-school friends set off on a quest to unravel the mystery of what drove a wedge between their grandmothers in the 1960s, an experience which leaves them pondering the continued legacy of slavery in their own lives today.